Average demands and most demanding passages of national-level female soccer matches: do small- and large-sided games replicate match demands? - Savolainen, E. H. J.; Vänttinen, T.; Peltonen, J.; Ihalainen, J. K.; Walker, S. (Frontiers in Sports and Active Living, 2023)
Study purpose: 1) determine the average and most demanding passage (MDP) load of national-level female soccer matches and 2) evaluate the relationship of average and MDP load during small- and large-sided-games (SSG and LSG) to those of the matches. Thirty-seven national-level female soccer players from a single club’s senior- and U18-teams participated. Average and 1-, 3- and 5-min MDP external (total, high-speed and very-high-speed running distances, acceleration and deceleration distances, average metabolic power and high-metabolic load distance) and internal loads (average heart rate, RPE) were analyzed from 29 league matches, 4v4 + goalkeepers SSGs and 8v8 + goalkeepers LSGs (both played twice) by Polar Team Pro player tracking system. The match’s external load variables during 1-, 3- and 5-min MDPs were 167-1165%, 135-504% and 126-359%, of match average values, respectively. In LSGs, all external load variables reached higher average values compared to matches, except very-high-speed running distance, but no variable reached higher 1-min MDP values compared to matches. In SSGs, average acceleration and deceleration distances were higher compared to matches. The findings from the present study suggest that LSGs and SSGs can be used to overload selected external load variables’ average values compared to matches, but other training options should be explored to overload match 1-min MDPs.